Molecular Study on The Pathogenicity of Avian Influenza Virus - Haryadi M. Wibowo; Heru Susetya; Tri Untari; Khrisdiana Putri; Charles Rangga Tabbu (Indonesian Journal of Biotechnology, 2006)
Highly pathogenic avian influenza virus (HPAI) differ from Low pathogenic avian influenza virus (LPAI) basedon multiple basic amino acid motif of the carboxylterminus of HA1, especially arginine and lysine. The propose ofthis work was toamplify and sequence the cleavage site region of HA gene of avian influenza virusisolated from bothcases with characteristic or unspecific lesion, using reversetranscriptase polymerase chain reaction (RT-PCR). Primerdesaigned for amplification and sequence was H5-F: 5’ ggagactcagcaatcccatgaaaag 3’ and H5-R:5’ccataccaaccgtctaccattcc 3’, and expected product size was 246 bp. The result indicated that all avian influenzavirus (AIV)-isolates originated from chicken with both specific and non specific lesion show a multiple basic aminoacid motif -PQRERRRKKR//GLF- and classified as highly pathogenic avian influenza. Philogenetic study of HAgenefragment indicated that each type of characteristic lesion created philo-groups.Key words: avian influenza, lesion, hemagglutinin, cleavage site, phylogeny.